2014
DOI: 10.1016/j.celrep.2014.05.032
|View full text |Cite
|
Sign up to set email alerts
|

ADAM17-Dependent c-MET-STAT3 Signaling Mediates Resistance to MEK Inhibitors in KRAS Mutant Colorectal Cancer

Abstract: There are currently no approved targeted therapies for advanced KRAS mutant (KRASMT) colorectal cancer (CRC). Using a unique systems biology approach, we identified JAK1/2-dependent activation of STAT3 as the key mediator of resistance to MEK inhibitors in KRASMT CRC in vitro and in vivo. Further analyses identified acute increases in c-MET activity following treatment with MEK inhibitors in KRASMT CRC models, which was demonstrated to promote JAK1/2-STAT3-mediated resistance. Furthermore, activation of c-MET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(142 citation statements)
references
References 38 publications
10
129
3
Order By: Relevance
“…Genes retrieved as being capable of synergizing with MEK silencing could be cataloged in two classes: members of the receptor tyrosine kinase family (RTKs) and elements of the RAF family of serine/threonine kinases. Blockade of RTKs (such as EGFR, HER3, IGF1R, and MET) in conjunction with MEK inhibition for KRAS mutant CRCs has been explored in several previous studies (Ebi et al, 2011;Molina-Arcas et al, 2013;Sun et al, 2014;Turke et al, 2012;Van Schaeybroeck et al, 2014). In this work, we focused instead on co-targeting RAFs and MEK.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Genes retrieved as being capable of synergizing with MEK silencing could be cataloged in two classes: members of the receptor tyrosine kinase family (RTKs) and elements of the RAF family of serine/threonine kinases. Blockade of RTKs (such as EGFR, HER3, IGF1R, and MET) in conjunction with MEK inhibition for KRAS mutant CRCs has been explored in several previous studies (Ebi et al, 2011;Molina-Arcas et al, 2013;Sun et al, 2014;Turke et al, 2012;Van Schaeybroeck et al, 2014). In this work, we focused instead on co-targeting RAFs and MEK.…”
Section: Discussionmentioning
confidence: 93%
“…ERK inhibitors are still in preclinical development, and their efficacy in KRAS mutant cancers has not been extensively investigated. However, previous works suggest that blockade of the EGFR-RAS-MEK axis with agents targeting a single node has often limited impact due to feedback reactivation of the signaling pathway (Ebi et al, 2011;Molina-Arcas et al, 2013;Sun et al, 2014;Turke et al, 2012;Van Schaeybroeck et al, 2014). Of relevance, it has recently been reported that BRAF mutant melanoma cells are often resistant to ERK inhibition, because the relief of ERK-dependent negative feedback can activate RAS and PI3K signaling (Carlino et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Western blotting was performed as described earlier (23). The Super Signal Chemiluminescent ECL Plus (Amersham) was used for protein detection.…”
Section: Western Blotting and Real-time Pcrmentioning
confidence: 99%
“…Another new interactor, Tensin-4, stabilizes MET exposure at the cell surface, promoting intensity and duration of the signal: its loss favors MET degradation and death of cells harboring amplification [54]. Finally, STAT3, previously characterized as an essential mediator of MET signaling in physiological invasive growth (branching morphogenesis) [55], has been recently shown to be critical to sustain the proliferative program of METamplified cells [56], and to sustain MET-mediated resistance of colorectal cancer to MEK inhibitors [57].…”
Section: Met Relies On Signaling Partners In Addicted Cellsmentioning
confidence: 97%